PYRAZOLE BEARING MOLECULES AS BIOACTIVE SCAFFOLDS: A REVIEW - Hira Aziz; Ameer Fawad Zahoor; Sajjad Ahmad (Journal of the Chilean Chemical Society, 2020)
Pyrazole being a heterocyclic motif has secured an eccentric status in the field of medicinal chemistry. Pyrazole and its derivatives have tremendous biological applications like anti-cancer, anti-microbial, antiviral, antifungal, anti-inflammatory, analgesic, insecticidal etc. In this review,  some recent developments  have been reported  for the synthesis of biologically active pyrazole  based molecules having biological potential such as anti-SIRT1 and SIRT2, anti-FAAH, anti-NOSs, as liver X receptor partial agonist, CB2 receptor ligand and glucagon receptor antagonists.